Post-socialist transition, authoritarian consolidation and social origin of political elites: the case of Russian regional governors. Issue 3 (4th May 2019) - Demin, Alexander; Libman, Alexander; Eras, Laura
ABSTRACT: The social origin of elites is important as it, first, affects the political decision-making, and second, is an indicator of social mobility important for the stability of a political system. However, how does the consolidation of an authoritarian regime affect the composition of elites in terms of their social origin? This study investigates this question looking at a sample of Russian regional governors in the period of 1992–2016. We document a gradual decrease of the share of governors from peasants' and workers' families, which is most likely related to abandoning the Soviet elite recruitment practices. At the same time, the main beneficiaries of the change (outside the ethnic regions) are not the most privileged groups (children of high-ranked bureaucrats and politicians) but rather offspring of intelligentsia (doctors, teachers and engineers). Interestingly, the military social origin became more important prior to Putin's presidency, during the era when Russian politics was more competitive and pluralist.